PENGARUH KUALITAS PELAYANAN TERHADAP LOYALITAS NASABAH KREDIT PADA SWAMITRA PT. BANK BUKOPIN TBK UNIT BULAKAN SUKOHARJO - Yusrin, Moch Tri Anggoro; Istiatin, Istiatin; Kustiyah, Eny (STIE AUB Surakarta)
Quality of care is the expected benefits of control over the level of excellence to meet the wishes of the customer.In field of services, as is done by Swamitra PT. Bank Bukopin Tbk, Unit Bulakan Sukoharjo, good quality services will effect on customer satisfaction. With the satisfaction felt by customers it will indirectly encourage customers to re-use the services and existing services giving rise loyalty.Goals to be achieved in this research is to determine the effect either simultaneously or partially dimensions of tangibles, reliability, responsiveness, empathy, and assurance on customer loyalty credits Swamitra PT. Bank Bukopin Tbk Unit Bulakan Sukoharjo.The method in this study using the customer population of Swamitra PT. Bank Bukopin Tbk,Â amounted to 617 people and 100 people are taken as samples. This study used a questionnaire as a data collection tool. It is using SPSS 22.0 for Windows to analyze the data. The technique of data analysis used is multiple linear regression analysis and simple linear regression analysis which serve to prove the hypothesis of the study. The results showed that both simultaneously and partially there is positive and significant dimensions of tangibles, reliability, responsiveness, empathy, danassurance on customer loyalty credits Swamitra PT. Bank Bukopin Tbk Unit Bulakan Sukoharjo. With the contribution of independent variables on the dependent variable (determination) of 85.60%. The conclusion of this study is there was a significant and positive effect of tangibles, reliability, responsiveness, empathy, and assurance on customer loyalty credits Swamitra PT. Bank Bukopin Tbk Unit Bulakan SukoharjoKeywords: Tangibles, Reliability, Responsiveness, Empathy, Assurance, and Loyalty.